PTH-114 Dedicated endoscopic ibd surveillance list improves adherence to guidelines. (17th June 2017) - Goldberg, R; Fong, S; Samaan, M; DigbyBell, J; Johnston, E; Anderson, S; Irving, P; Sanderson, J
Abstract : Introduction: Current guidelines propose surveillance colonoscopy for patients with long term colonic Crohn's disease or ulcerative colitis. Guidelines also suggest using chromoendoscopy with targeted biopsies of abnormal areas. Previous audits have shown poor adherence to these recommendations. We report the assessment of an IBD surveillance colonoscopy programme in an IBD tertiary centre, having implemented interventions in order to improve the quality of the service provided. Method: To assess the efficacy of introducing dedicated IBD surveillance lists along with a change in bowel preparation and the use of post-endoscopy virtual clinics on the quality of the surveillance survey. We compared 2 different periods before and after the measures were implemented (period A (pre intervention): August 2015-December 2015 and period B (post intervention): August 2016-December 2016) Results: A total of 84 patients underwent IBD surveillance colonoscopy, 28 in period A and 56 in period B. 16 out of 28 patients (57.1%) were allocated to an IBD endoscopy list in period A and 51/56 (91%)of patients in period B. During period B, 40/51 (78.5%) were allocated to a newly established dedicated IBD chromoendoscopy surveillance list. Chromoendoscopy was performed in 14/28 (50%) patients in Period A and in 44/56 (78.6%) patients in Period B. Dedicated surveillance list was significantly correlated with the use of chromoendoscopy (p=0.02). In addition, dedicated IBD surveillance list was correlated with targeted biopsies ( p :0.009). Despite these differences, the detection of abnormal lesions was similar (18/28 (64.2%) patients in period A and in 34/56 (60.7%) in period B). Likewise, dysplasia was detected in 6/28 (21.4%) patients in period A and in 8/56 (14.3%) in period B. All cases of dysplasia were detected on targeted biopsies whereas no dysplasia was found on random biopsies. However, in both periods, lesion detection rate was significantly associated with performance of chromoendoscopy (p=0.04). There was no significant difference in the number of patients that had good or adequate bowel preparation (BBPScale:2 or 3)( p : 0.9607) when sodium picosulphate was compared to Moviprep. There was a trend for correlation for good bowel prep (BBPS:3) and adenoma detection (p=0.082). Significantly more follow up endoscopies were arranged once patients were channelled through a newly established IBD virtual clinic (33/40 vs 10/44 p<0.05) Conclusion: Following the implementation of a dedicated IBD surveillance, the use of chromoendoscopy and targeted biopsies has increased significantly and capacity for effective surveillance endoscopy doubled. We suggest these strategies should be considered in IBD centres to help improve the uptake and performance of an effective IBD surveillance programme. Disclosure of Interest: None Declared